Natural Frequency Analysis on The Base Structure of The CNC Milling Machine Using Simulation and Experimental Methods - Tinulad, Amar Makruf; Fikry, Veky M. (Majalah Ilmiah Pengkajian Industri; Journal of Industrial Research and Innovation, 2023)
The development of national machine tools needs special attention in order to compete with foreign products. Government agency cooperates with industry partners to develop precision CNC milling tools at competitive prices in today's manufacturing industry. One of the problems that often occur in the machine structure is the vibration caused by the resonance between the components that make up the machine, which results in inaccurate machining products. Therefore, it is necessary to do a natural frequency analysis on the milling machine prototype. This research was conducted on the base structure which is the most basic component as a holder for other components. Natural frequency analysis on the base structure uses two methods, namely experimental and numerical simulation using FEA. The results of the two methods are then compared and analyzed for errors that occur. Research parameter so that design does not resonate is that rotational velocity should be 15% above or below the natural frequency. The results show comparison natural frequency error value of numerical simulation method with experimental method and analysis of safety base design against resonance.